Stereospecific α-glucosidase inhibition, kinetics, and molecular docking studies on isolated diastereomeric alkaloids from Uncaria longiflora - Nurul Aina Suzlin, Sulaiman; Muhammad Farhan Syakir, Nor Azman; Mohd Fadhlizil Fasihi, Mohd Aluwi; Zainul Amiruddin, Zakaria; Mohammad Jemain, Mohammad Ridhwana; Fatimah, Salim (Elsevier B.V., 2025)
The stem extract of Uncaria longiflora var. pteropoda (Rubiaceae) has been reported to possess strong α-glucosidase inhibition. However, the specific compounds contributing to this inhibitory potential have not yet been determined. The aim of the present work was to isolate phytochemicals from the methanolic stem extract of the plant and evaluate the isolated compounds for their antidiabetic potential. Phytochemicals isolation was conducted using various chromatographic methods, with purification achieved through recycling high-performance liquid chromatography (rHPLC) and elucidation performed using various spectroscopic techniques. The antidiabetic potential was evaluated through in vitro α-glucosidase inhibition, kinetics, and molecular docking studies. The crude methanolic extract exhibited α-glucosidase inhibition with IC50 of 138.10 ± 1.32 μg/mL, significantly higher than the previously reported value. Phytochemistry work yielded C-7 diastereomeric pentacyclic oxindole alkaloids (POAs), known as pteropodine and isopteropodine. Kinetics analysis revealed that pteropodine and isopteropodine inhibited α-glucosidase through competitive and noncompetitive mechanisms, with IC50 values of 226.70 ± 2.82 and 98.06 ± 1.98 µg/mL, respectively. Molecular docking and electrostatic potential studies confirmed pteropodine’s interaction with the active sites (Asp349, 1.70 Å and Glu276, 2.94 Å) of α-glucosidase and isopteropodine’s binding to allosteric sites. Although the high concentrations required for effective enzyme inhibition may limit the practical application of these compounds as antidiabetic therapies, this study provides valuable insights into the chemistry underlying the plant’s previously reported antidiabetic potential, particularly in a stereospecific context. The findings further support the unique biological activities attributed to the diastereomeric alkaloids, highlighting their importance in understanding the plant’s therapeutic potential.